Arctic Continental Margin Sediments as Possible Fe and Mn Sources to Seawater as Sea Ice Retreats: Insights From the Eurasian Margin. Issue 8 (18th August 2020) - Tessin, Allyson; März, Christian; Blais, Marie‐Amélie; Brumsack, Hans‐Juergen; Matthiessen, Jens; O'Regan, Matt; Schnetger, Bernhard
Abstract: Continental margins are hot spots for iron (Fe) and manganese (Mn) cycling. In the Arctic Ocean, these depositional systems are experiencing rapid changes that could significantly impact biogeochemical cycling. In this study, we investigate whether continental margin sediments north of Svalbard represent a source or sink of Fe and Mn to the water column and how climate change might alter these biogeochemical cycles. Our results highlight that sediments on the Yermak Plateau and Sofia Basin exhibit accumulations of Fe and Mn phases compared to average shale. Conversely, sediments from the Barents Sea slope exhibit lower enrichments of Fe and Mn compared to average shale, with the exception of enriched, near‐surface sediment layers. Pore waters from these slope sites provide evidence for Fe and Mn reduction and diffusion of Fe and Mn into near surface sediments, which are susceptible to physical or biogeochemical remobilization. These regional patterns are best explained by the spatial distribution of sea ice coverage and labile organic carbon fluxes to the seafloor. As sea ice continues to retreat and the Yermak Plateau becomes seasonally ice‐free, productivity is expected to increase, which would increase the flux of carbon to the sediments, thereby increasing oxidant demand, and the reduction of Fe and Mn mineral phases. Our results suggest that as sea ice continues to retreat, the Yermak Plateau and other Arctic continental margins could become sources of Fe and Mn to Arctic bottom waters. Key Points: Reactive iron and manganese are accumulated at Yermak Plateau sites but recycled at Barents Sea slope sites regardless of water depth Sea ice extent and export of surface carbon likely create different benthic oxidant demands, which drives differences in metal accumulation As sea ice extent and ocean currents change, the Yermak Plateau and other Arctic margins may become sources of metals to the water column